A Study on User's Opinion About Library Staff and Use of Library Services in Scientific and Research Institute Libraries in Iran - Khademizadeh, Shahnaz; Venkatesha, Y. (Journal of Information and Knowledge, 2014)
This article aims to know the users' opinion about the library collections and services. For the purpose of data collection the survey method using a questionnaire has been applied. Further, an attempt has been made to identify how the users are satisfied with the library staff's help and cooperation. The article also concentrates on the areas of research where the researchers seek help from the library staff. This study finds that concerned authorities of Scientific and Research Institute libraries in Iran in specific and all the libraries in general, will take necessary steps to implement collection development techniques in their respective libraries, thereby serve their users better and recommends that application of advanced technology will increase the number of library users and also satisfy the present need of the users.